Nonsyndromic Bilateral Posterior Maxillary Supernumerary Teeth: A Report of Two Cases and Review - Ravi Kumar Mahto; Shantanu Dixit; Dashrath Kafle; Aradhana Agarwal; Michael Bornstein; Sanad Dulal (Case Reports in Dentistry)
Supernumerary tooth/hyperdontia is defined as those teeth which are present in excess of the usual distribution of twenty deciduous and thirty-two permanent teeth. It can be seen in both syndromic and nonsyndromic patients. In Nepalese population, prevalence of supernumerary tooth is documented to be 1.6%. To the best of our knowledge, no studies from Nepal have reported the incidence of bilateral maxillary paramolars or the combination of unilateral maxillary paramolar and distomolar till date. Hence, we are reporting these two cases with a brief review of literature to put emphasis on incidence, prevalence, proposed hypothesis for etiology, and management of supernumerary teeth.